Long-term conditions a guide for nurses and healthcare professionals - Randall, Sue; Ford, Helen, 1967- (Wiley-Blackwell, 2011)
"Long-Term Conditions is a comprehensive textbook for all nursing and health care students and practitioners, that explores the key issues surrounding caring for patients with chronic diseases or long -term conditions. Divided into three sections, this book explores living with a long-term condition; empowerment; and care management. Rather than being disease focused, it looks key issues and concepts which unify many different long-term conditions, including psychological and social issues that make up a considerable part of living with a long-term condition. Within each of the chapters, issues of policy, culture and ethics are intertwined, and case studies are used throughout, linking the concepts to specific diseases. Key features: A comprehensive textbook on the principles and practice of caring for people with long -term conditions User-friendly in style with learning outcomes, further reading, useful websites, and case studies throughout linking to specific conditions Moves away from a disease focused medical model, and takes a needs-led approach Uniquely explores the overarching issues of living with one or more long- term conditions, Focuses on the importance of multi-disciplinary team work and collaborative teamwork in the management of long- term conditions"--Provided by publisher.